STUDI ISOTERM DAN KINETIKA ADSORPSI PADA PENYISIHAN BUANGAN AKHIR POME MENGGUNAKAN MAGNETIC BIOCHAR SEBAGAI ADSORBEN - Kesni savitri; Andrio, David; Helwani, Zuchra (KURVATEK, 2022)
Research on kinetics and adsorption isotherm modelling of POME final discharge using magnetic biochar from palm fronds to remove COD, TSS and color has been performed. The synthesis, characterization and magnetic adsorption test of biochar have been successfully carried out. Magnetic biochar is made by impregnating palm fronds using FeCl3.6H2O for 3 hours and pyrolysis using horizontal fixed bed reactor with 0,2 l/minute N2 flow rate at 550oC for 20 minutes. The adsorption data of COD,TSS and Color were described well by the Langmuir isoterm with R2 value of 0,9869;0,9795; 0,9972. The kinetics model were described by the pseudo-second-order model with a R2 value 0,9789; 0,9942; 0,9550. Based on the results of the isotherm model and kinetics of COD, TSS and color adsorption, occurred due to chemical bonds in the presence of monolayer adsorbate on the surface of magnetic biochar.